Comparison of panoramic mandibular cortical bone quality indexes in amlodipine users and healthy individuals - Aga Satria Nurrachman; Lusi Epsilawati; Azhari Azhari; Suhardjo Sitam (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Hypertension and osteoporosis are believed to be linked to to each other. Previous studies have suggested that the imbalance of calcium metabolism in hypertensive condition and the use of calcium channel blockers such as amlodipine may lower the density and quality of bone. Panoramic radiography has been widely used as a reliable tool in assessing bone quality. One indicator of bone quality in panoramic radiograph is the macrostructure evaluation of mandibular cortical bone by using various indexes such as mandibular cortical index (MCI) and antegonial index (AI). This research aimed to compare the bone quality of hypertensive patients with amlodipine and healthy individuals using MCI and AI. In this study we used sixty panoramic radiographs of hypertensive patients with amlodipine and healthy individuals, thirty for each group, with various aspects of demography. The MCI analysis was done by dividing the mandibular cortical shape into three different qualitative categories and the AI analysis was done quantitatively by measuring the width of mandibular cortical bone in antegonial region using ImageJ software. There were statistically significant differences in the results between the two groups in terms of both AI (p = 0.000) and MCI (p = 0.001) in which hypertensive group had lower score. Based on this research, there were differences of mandibular bone quality of hypertensive patients with amlodipine and healthy individuals, particularly in its macrostructure.